1960
DOI: 10.1083/jcb.7.4.667
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Proliferation of Intestinal Epithelia in the Rat Two Months after Partial Resection of the Ileum

Abstract: Sprague-Dawley rats subjected 2 months previously to partial resection (10 per cent) of the small intestine and their controls were injected with tritiated thymidine and sacrificed at 2 and 23 hours. Segments of the duodenum, jejunum, and ileum were autoradiographed, and the migration of the labelled cells during the period between 2 and 23 hours was measured with an eyepiece micrometer. The cells had migrated 35, 42, and 34 per cent of the total distance from thecrypts to the tips of the villi in the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
25
0

Year Published

1963
1963
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(31 citation statements)
references
References 6 publications
6
25
0
Order By: Relevance
“…The life span of an epithelial cell on the villus in the duodenum, jejunum, and ileum, respectively, of resected rats was 82, 46, and 42 per cent of the control values. Our data confirm the findings of the previous study (1).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The life span of an epithelial cell on the villus in the duodenum, jejunum, and ileum, respectively, of resected rats was 82, 46, and 42 per cent of the control values. Our data confirm the findings of the previous study (1).…”
Section: Discussionsupporting
confidence: 83%
“…The increased rate of migration of intestinal crypt cells onto villi in the present study was of the magnitude that would be expected from the previously reported reduction in the life span of epithelial cells in the jejunum and ileum of resected rats (1). In the duodenum of resected rats, the epithelial cells emerge from the crypts and move up the villi at nearly normal rates and have a nearly normal life span.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…This physiological activation of the remnant intestine corresponds with histological alterations wherein villus height and cell mitosis numbers were higher in all intestinal segments of jejunal resection groups. This structural reconstruction after intestinal resection corresponds to results in other studies; rats showed an increased cell population in the colonic crypt (Zufarov and Baibekov, 1971) and an elevated cell migration rate and villus height (Loran and Althausen, 1960) in the remnant intestine after intestinal resection. Hypertrophied villus height (Navidshad et al, 2010) and cell mitosis numbers (Buwjoom et al, 2010) were reported with increased body weight in intact chickens, suggesting that remnant villi in this study were also hypertrophied.…”
Section: Discussionsupporting
confidence: 89%